A finite element study on the nonlinear behavior of rectangular shear panels. (July 2016) - Rasool, Mehnaz; Singha, M.K.
Abstract: Shear deformable finite element method is employed here to investigate the stability characteristics of isotropic and composite shear panels. The effects of in-plane boundary conditions (non-uniform pre-buckling stresses and development of a compression strip ) and out-of-plane restraints against bending / torsion of the edges on the shear buckling loads of isotropic rectangular plates are examined at the beginning. Buckling loads of laminated composite plates are studied with an attempt to correlate the fiber orientation with the compression strip . Limited parametric study has been conducted to examine the postbuckling behavior of perfect, imperfect and eccentrically loaded thin rectangular plates with various practical boundary conditions. Highlights: Nonlinear stability behavior of shear panels with various boundary conditions is investigated. In-plane shear in rectangular plates develops a compression strip . The buckling strength of composite shear panels depends on the flexural rigidity along the compression strip . The lateral and torsional buckling of eccentrically loaded cantilever shear panels are examined. The stability characteristics of shear panels under combined in-plane shear and compressive load are investigated.